Numeracy Literacy Capability of Junior High School Students at Inamosol District - Laamena, Christina M.; Ayal, Carolina S.; Talib, Taufan (KnE Social Sciences, 2024)
It is important for students to master numeracy literacy as part of the minimum competency assessment, in order to have the thinking skills needed in the 21st century. This research aims to describe the numeracy literacy abilities of junior high school students in mountainous areas. This research uses a mixed method. The data collected is quantitative in the form of numeracy literacy test results and qualitative data in the form of interview results to describe students’ weaknesses in numeracy literacy. The research results showed that student’s literacy skills still remain at levels 1 and 2. Less than 20% of students were at level 3, and there were no students at levels 5 and 6. The category of students is that intervention and basic literacy skills are needed. The qualitative analysis concluded that the cause of low literacy was low communication, mathematization, and representation skills. In terms of indicators of mathematical ability, there are various basic concepts that students have not mastered so they experience difficulty in solving mathematical problems. Apart from that the reasoning that occurs is still imitation in nature, students still tend to memorize and use standard and imperfect procedures. The strategy used only imitates the teacher’s strategy, while students have not used new strategies which causes literacy to still be at a lower level. Keywords: numeracy, literacy, numeracy literacy level, mountains areas